Исследование спектров фотолюминесценции низкоразмерных структур InSb, сформированных в матрице GaSb - Andronova, E. V.; Baganov, Ye. A.; Kurak, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
Results of investigation of photoluminescence spectrums of the epitaxial structures containing InSb low-dimensional structures formed in GaSb matrix by a method of pulse cooling of saturated solution-melt are presented. It is shown, that observable photoluminescence bands are concerned with radiation transitions through energy levels of InSb low-dimensional structures formed on InSb wetting layer with thickness of 2 nm.